Synthesis of an Insulated Oligo(phenylene ethynylene) Dimer Through Cyclodextrin-Based [c2]Daisy Chain Rotaxane - Susumu Tsuda; Naoto Yasumura; Shin-ichi Fujiwara; Yutaka Nishiyama (Molbank)
Oligo(phenylene ethynylene)s (OPEs) are π-conjugated systems with promising optical, bioactive, and electrical properties, making them valuable candidates for molecular electronics and biosensors. Controlling the arrangement and orientation of π-conjugated systems is crucial in developing molecular devices. Recently, we developed insulated diarylacetylene dimers using a [c2]daisy chain rotaxane strategy, which brings two cores into close proximity without covalent bonding and shields them with permethylated α-cyclodextrins. Here, we synthesized an insulated OPE dimer using a similar rotaxane strategy to investigate its optical properties. The rotaxane structure and optical properties were evaluated using nuclear magnetic resonance (NMR) spectroscopy, electrospray ionization high-resolution mass spectrometry (ESI-HRMS), and absorption and fluorescence spectroscopy. This study is expected to contribute to the development of optical and electronic materials utilizing OPEs.